Use of pesticides for the control of the main subterranean upland rice pests - Martins, José Francisco da Silva; Ferreira, Evane; Prabhu, Anne Sitarama; Zimmermann, Francisco José Pfeilsticker (Pesquisa Agropecuaria Brasileira, 2014)
Three field experiments were conducted to study the implications of the soil and seed treatments with chemical products for the control of main subterranean insect pests of rice under upland conditions. It was observed that the higher initial plant stand obtained due to treatment effects did not reflect in increased grain yield. The higher initial emergence of the plants with the proportional increase in tiller number per unit area during the vegetative phase favoured blast incidence which either failed to increase the yields or resulted in decrease in grain yields when principally the drought stress occurred during the reproductive phase.